Assessing the Targeting System in Georgia : Proposed Reform Options - Honorati, Maddalena; Sormani, Roberto Claudio; Carraro, Ludovico (World Bank, Washington, DC, 2020)
This paper investigates reasons of Georgian targeted social assistance (TSA)’s declining performance and presents a new proxy means test (PMT) model estimated on the most recent household income and expenditure survey data (2018). The paper finds that the presented updated formula performs better in terms of its ranking property, coverage of the poor, and benefit incidence among the poor. The updated PMT formula will improve the coverage of the poorest decile by raising it from 69 percent to 77 percent and the benefit incidence in the poorest decile from 60 to 65 percent. The analysis also finds that most of the winners are in the poorest quintile while the losers in the top quintiles. In the medium term, the paper highlights the potential benefits of moving to a hybrid targeting approach, whereby reported income is used as a first-stage exclusion criterion before a PMT assessment.